Development of microencapsulated phase change material with poly (methyl methacrylate) shell for thermal energy storage. (February 2019) - Su, Weiguang; Zhou, Tongyu; Li, Yilin; Lv, Yuexia
Abstract: This research focused on the development of MEPCMs for thermal energy storage in low carbon buildings with poly (methyl methacrylate) (PMMA) shell. The experimental results showed that the best MEPCM sample was prepared with 1 wt% of the thermal initiator and the surfactant of S-1DS. The differential scanning calorimetric (DSC) analysis showed that the best sample has a latent heat of 170 kJ/kg and a melting temperature of 22.68 ℃. Meanwhile, the core material contents and encapsulation efficiencies were calculated according to the measured results of the DSC. Those two values for the sample of PMMA-3 and PMMA-5 were even higher than theoretical values due to the evaporation of shell monomer during encapsulation processes. Finally, the thermogravimetric (TG) analysis of the fabricated MEPCM samples showed good thermal stability behaviors above 161 ℃ and therefore satisfy the environmental requirements for most applications.